Absorption and Desorption of Sulphur Dioxide in Ethylene Glycol + Water Binary System - Zhang, Jianbin; Zhang, Yongfeng; Bai, Jie; Li, Chunping (Asian Journal of Chemistry, 2012)
In previous work, considering the industrial flue gas desulphurization (FGD) processes, F1 = 80 % EGW (ethylene glycol + water) (ca. 0.5 molar fraction of ethylene glycol) was confirmed as the optimum composition of desulphurization solution. The present work was used to provide absorption and desorption apparatus for the flue gas desulphurization processes using simulate flue gas. The present work showed that the absorption rate of 1058 ppm SO2/N2 mixture was decreased into 177.2 ppm when the gas-liquid ratio is 3. In the process, the desulphurization rate arrived at 83 %. Meanwhile, in the desorption process, the concentration of SO2 in the 80 % EGW were changed from 37.9 mg/L into 1.7 mg/L and the desorption rate arrived at 95 %.